Pertanggungjawaban Koperasi Dalam Pemutusan Hubungan Kerja Anggota: Studi Kasus Putusan MA No. 361 K/Pdt.Sus-PHI/2024 - Ati, Ditia Prabandari Laras; Rambe, Fitri Rahmadani; Syajidah, Hanna Alicia; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2026)
The liability of cooperatives in terminating the employment of their members is an important issue in both labor law and cooperative law. This study examines the Supreme Court Decision Number 361 K/Pdt.Sus-PHI/2024, which affirms that a cooperative remains positioned as an employer when a genuine employment relationship exists. Unilateral termination of employment without proper procedures and without fulfilling workers’ normative rights is deemed unlawful. The analysis is based on Law No. 13 of 2003 on Manpower, Law No. 25 of 1992 on Cooperatives, and relevant literature indicating that cooperatives are obliged to provide severance pay, long-service awards, and compensation for workers’ rights. The findings emphasize that cooperative management may be held administratively and materially liable for unlawful termination, and that this decision constitutes an important precedent for the protection of members who also hold the status of workers..